2015
DOI: 10.1371/journal.pone.0145310
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson Symptoms and Health Related Quality of Life as Predictors of Costs: A Longitudinal Observational Study with Linear Mixed Model Analysis

Abstract: ObjectiveTo estimate the magnitude in which Parkinson’s disease (PD) symptoms and health- related quality of life (HRQoL) determined PD costs over a 4-year period.Materials and MethodsData collected during 3-month, each year, for 4 years, from the ELEP study, included sociodemographic, clinical and use of resources information. Costs were calculated yearly, as mean 3-month costs/patient and updated to Spanish €, 2012. Mixed linear models were performed to analyze total, direct and indirect costs based on sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…PD costs increase over time and are significantly affected by motor symptoms. 27 Garcı´a Ramos et al (2013) 28 reviewed all published data regarding PD costs in Spain and reported total costs of E8640 per semester, with direct costs (E6030) being the biggest contributor. 27 Von Campenhausen et al (2011) 29 demonstrated that PD total costs of per semester, from the societal perspective, were lower in Eastern European countries (Russia: E2620; Czech Republic: E5510) as compared with most Western European countries (Austria: E9820; Germany: E8610; Italy: E8340).…”
Section: Discussionmentioning
confidence: 99%
“…PD costs increase over time and are significantly affected by motor symptoms. 27 Garcı´a Ramos et al (2013) 28 reviewed all published data regarding PD costs in Spain and reported total costs of E8640 per semester, with direct costs (E6030) being the biggest contributor. 27 Von Campenhausen et al (2011) 29 demonstrated that PD total costs of per semester, from the societal perspective, were lower in Eastern European countries (Russia: E2620; Czech Republic: E5510) as compared with most Western European countries (Austria: E9820; Germany: E8610; Italy: E8340).…”
Section: Discussionmentioning
confidence: 99%
“…The first includes tremor, rigidity, bradykinesia, and postural instability. Non-motor symptoms are various and includes loss of taste and sense of smell, sleep disturbances, gastrointestinal complications, constipation, swallowing problems, anxiety, pain, fatigue, depression, sexual dysfunction, hallucinations and psychosis, impulse control disorders, cognitive impairment, and dementia [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Satisfactory internal consistency, inter-rater and test-retest reliability and construct validity have been reported ( 92 ). It is also responsive to changes over time ( 93 ) and can predict an increase in PD-related costs ( 94 ).…”
Section: Movement Disorders and Rating Scalesmentioning
confidence: 99%